PARTISIPASI MASYARAKAT DESA KOMODO DALAM PENGEMBANGAN EKOWISATA DI PULAU KOMODO - Modestus Ziku, Rafael (JURNAL MASTER PARIWISATA, 2015)
The purpose of this study was to examine the participationof community members of Komodo village with regard toecotourism development in the island of Komodo, KomodoNational Park, West Manggarai Regency. For the purpose ofthe study, qualitative research method was applied with theapplication of qualitative data collection techniques, includinginterviews, observation, and documentary analysis. Specifically,the study was conducted in the village of Komodo withactive participation of 22 key informants. The results of thisstudy revealed the roles of the community of Komodo villageparticipation in ecotourism development, namely communitymembers’ participation in the program of Komodo TourismVillage of BNI (Bank Negara Indonesia), participation inecotourism business, and participation in conservation. Factorsthat affect Komodo village community participation weredivided into two main factors, such as factors that support andfactor that hinder the community participation. The result alsoindicated the positive impact of the community participation oneconomic, environment, and social and cultural.